PENGARUH PERCEIVED VALUE, KEPUASAN PELANGGAN, KEPERCAYAAN PELANGGAN TERHADAP LOYALITAS PELANGGAN PADA OUTLET NIKE DI JAKARTA - Sebastian, Aaron; Pramono, Rudy (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
This study was conducted to determine the effect of perceived value, customer satisfaction, customer trust on customer loyalty at Nike outlets in Jakarta. This research was conducted in the city of Jakarta by involving 114 consumers in the category of men and women in the millennial generation. This data was collected by distributing a questionnaire containing 48 questions and by selecting a Likert scale of 1 – 5 based on a non-probability sampling method with a convenience sampling technique. The data analyzed by the researcher used the SEM software method based on the SmartPLS 3 system. The results of this study indicate that perceived value has a positive effect on customer loyalty and customer satisfaction. The results of this study also show that customer satisfaction has a positive effect on customer trust and customer trust has a positive effect on customer loyalty. The results of this study found that customersatisfaction has a positive effect on customer loyalty. This research can be used as input for Nike outlets to provide better service to consumers, so that consumers not only have satisfaction with a product but also can have loyalty and high expectations for Nike products.